Uprising - Haddix, Margaret Peterson (New York : Scholastic, 2007)
In 1927, at the urging of twenty-one-year-old Harriet, Mrs. Livingston reluctantly recalls her experiences at the Triangle Shirtwaist factory, including miserable working conditions that led to a strike, then the fire that took the lives of her two best friends, when Harriet, the boss's daughter, was only five years old. Includes historical notes.
Keywords: Triangle Shirtwaist Company -- Fire, 1911 -- Juvenile literature; Triangle Shirtwaist Company -- Fiction; Triangle Shirtwaist Company -- Fire, 1911 -- Fiction; Immigrants -- Juvenile sound recordings; Factories -- Juvenile sound recordings; Labor disputes -- Juvenile sound recordings; Strikes and lockouts -- Juvenile sound recordings; Immigrants -- Fiction; Factories -- Fiction; Labor disputes -- Fiction; Strikes and lockouts -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Juvenile sound recordings; New York (N.Y.) -- History -- 1898-1951 -- Fiction; Audiobooks